2018
DOI: 10.3389/fnins.2018.00775
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Inhibits Visceral Nociception via Somatovisceral Interaction at Subnucleus Reticularis Dorsalis Neurons in the Rat Medulla

Abstract: Electroacupuncture (EA) is an efficacious treatment for alleviating visceral pain, but the underlining mechanisms are not fully understood. This study investigated the role of medullary subnucleus reticularis dorsalis (SRD) neurons in the effects of EA on visceral pain. We recorded the discharges of SRD neurons extracellularly by glass micropipettes on anesthetized rats. The responses characteristics of SRD neurons to different intensities of EA (0.5, 1, 2, 4, 6, and 8 mA, 0.5 ms, and 2 Hz) on acupoints “Zusan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In fact, many human and animal studies have shown that EA with different intensities activated different types of peripheral afferent fibers and produce different extents of analgesia ( Xu et al, 2003 ; Zhu et al, 2004 ; Xin et al, 2016 ). Some studies have shown that EA with high-intensity stimulation is more effective than low-intensity stimulation of EA ( Barlas et al, 2006 ; Yu et al, 2018 ; Lv Z. T. et al, 2019 ). Conversely, some contrary conclusions have also been reported in animal studies ( Lee et al, 2005 ; Ceccherelli et al, 2008 ), which implies the necessity to explore the appropriate intensity of EA in the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many human and animal studies have shown that EA with different intensities activated different types of peripheral afferent fibers and produce different extents of analgesia ( Xu et al, 2003 ; Zhu et al, 2004 ; Xin et al, 2016 ). Some studies have shown that EA with high-intensity stimulation is more effective than low-intensity stimulation of EA ( Barlas et al, 2006 ; Yu et al, 2018 ; Lv Z. T. et al, 2019 ). Conversely, some contrary conclusions have also been reported in animal studies ( Lee et al, 2005 ; Ceccherelli et al, 2008 ), which implies the necessity to explore the appropriate intensity of EA in the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, ACC mediated the modulatory effect of EA on abdominal pain in IBS rats, and this effect was influenced by the distribution of acupoints. In addition, the role of medullary subnucleus reticularis dorsalis-ACC loop in reducing visceral hypersensitivity has also been suggested ( Yu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, additional studies have shown that ginger moxibustion, characterized by fluctuating temperature, and mild moxibustion techniques effectively induce acupoint sensitization, achieving better treatment outcomes than laser moxibustion, which involves stable temperature application ( Sun et al, 2021 ). Two additional studies documented noteworthy suppression of visceral hypersensitivity resulting from neuronal activity within the subnucleus reticularis dorsalis and wide dynamic range regions, employing EA at intensities ranging from 2 to 6 mA ( Yu et al, 2018 ; Yu et al, 2019 ). These pieces of evidence indicate that in the investigation of the neural mechanisms underlying the relief of VH, there is a relatively concentrated focus on the selection of acupoints.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, high-frequency EA stimulation is more effective than low-frequency stimulation. 18,19 Acupuncture also follows that (e.g. 120–180 rotations per minute).…”
Section: Influence Of Parametersmentioning
confidence: 97%